Pathogenic potential of soil fusaria from Malaysian oil palm habitats - Ho, Yin Wan; Varghese, George (Paul Parey Scientific Publishers, 1986)
A total of 353 Fusarium isolates consisting of 8 species and 2 varieties obtained from the soils of 22 sampling sites in oil palm habitats in Peninsular Malaysia was tested on 2-leaf stage oil palm seedlings. None of the isolates tested produced any symptoms of vascular wilt or other diseases. However, some of the isolates did have an adverse effect on the growth and vigour of the palms. They were found to cause significant reduction in palm growth. Isolates causing a reduction in the growth of the oil palm seedlings were not confined to a certain type of soil or a particular location.